Unravelling the role of TET2 in venous thromboembolism: insights into mechanisms and therapeutic implications - Yujie Bai; Yujie Bai; Xiao Wang; Ning Lin; Rongyuan Li; Weilin Hu; Jiayu Wang; Jiayu Wang; Chun Chen; Chun Chen; Jie Liu; Jian Feng; et al. (Frontiers in Cardiovascular Medicine, 2025)
The development of venous thromboembolism (VTE) may complicate not only the management of the primary disease but also significantly affect the overall quality of life and prognosis for the patient. With the increasing understanding of the incidence and risks associated with VTE, there is an imminent need for better management strategies, coupled with a wider knowledge base. In recent years, Ten-Eleven Transformation 2 (TET2) has become a subject of interest among medical scientists because of its function as DNA demethylase for the treatment of a number of hematologic and oncologic disorders. The current literature concerning the association of VTE with mutations in the TET2 gene is rather diverse in terms of outcomes and, therefore, not completely coherent. While some papers propose that TET2 has an antithrombotic effect, others point to a prothrombotic effect or a more subtle effect of TET2 on the development of thromboembolism. These different views must then be integrated in order to create the aetiologic narrative of TET2 in VTE that provides a framework for understanding the epidemiologic and clinical realities. However, there is no review on the mechanism and clinical significance of TET2 in venous thromboembolism. In this review article, the authors strived to investigate Ten-Eleven Transformation 2 (TET2) connected with venous thromboembolism (VTE), analyze its molecular mechanism features and draw clinical conclusions. It is the purpose of this work to perform a comprehensive review of the TET2 function, to elucidate its involvement in VTE development, and to discuss possible treatments based on targeting TET2. It is our understanding that the review of the current literature will offer fresh insight and research agendas for the future endeavours and practice of the significant medical speciality.